Tropoelastin and Elastin Assembly - Ozsvar, Jazmin; Yang, Chengeng; Cain, Stuart A.; Baldock, Clair; Tarakanova, Anna; Weiss, Anthony S. (Frontiers in Bioengineering and Biotechnology, 2021)
Elastic fibers are an important component of the extracellular matrix, providing stretch, resilience and cell interactivity to a broad range of elastic tissues. Elastin makes up the majority of elastic fibers and is formed by the hierarchical assembly of its monomer, tropoelastin. Our understanding of key aspects of the assembly process have been unclear due to the intrinsic properties of elastin and tropoelastin that render them difficult to study. This review focuses on recent developments that have shaped our current knowledge of elastin assembly through understanding the relationship between tropoelastin’s structure and function.